Prohibitin 2: At a communications crossroads. Issue 4 (21st April 2015) - Bavelloni, Alberto; Piazzi, Manuela; Raffini, Mirco; Faenza, Irene; Blalock, William L.
Abstract: Prohibitins (PHBs) are a highly conserved class of proteins first discovered as inhibitors of cellular proliferation. Since then PHBs have been found to have a significant role in transcription, nuclear signaling, mitochondrial structural integrity, cell division, and cellular membrane metabolism, placing these proteins among the key regulators of pathologies such as cancer, neuromuscular degeneration, and other metabolic diseases. The human genome encodes two PHB proteins, prohibitin 1 (PHB1) and prohibitin 2 (PHB2), which function not only as a heterodimeric complex, but also independently. While many previous reviews have focused on the better characterized prohibitin, PHB1, this review focuses on PHB2 and new data concerning its cellular functions both in complex with PHB1 and independent of PHB1. © 2015 IUBMB Life, 67(4):239–254, 2015